Water requirement of rice crop using CROPWAT model for Dehradun district, Uttarakhand - VERMA, RAMESH; JAISWAL, SMITA; GANGWAR, ANSHU; SHARMA, GAURAV; BHADAURIA, PRADEEP KUMAR SINGH (Journal of Soil and Water Conservation, 2021)
Management of water resources with optimal utilization results in fulfilling the constraint of inadequate water availability. Determination of crop water requirement is the first step in planning and effective utilization of irrigation water which curtaining the impact developed due to water stress condition. In the present study crop water requirement (CWR) and irrigation requirement was computed for rice in Dehradun district using CROPWAT simulation software by taking into account different local climatic parameter which influencing reference crop evapotranspiration (ET0) and thus affecting crop production. Penman–Monteith method was used to calculate ET0 and the United States Department of Agriculture (USDA) soil conservation method was used to estimate the effective rainfall. The ET0 varied from 1.43 (January) to 5.28 (May) mm/day and annual mean was 3.1 mm/day. The average annual rainfall value was 1718 mm and out of which 977.3 mm was effective rainfall. The crop water requirement and net irrigation water requirement (NIR) for rice crop was estimated to be 559.5 mm and 288.7 mm, respectively. The values of CWR and NIR were maximum in June and minimum in October. The net scheme irrigation requirement was scheduled to be maximum in June (190.6 mm/month), minimum in October month and zero in the month of July, August and September. The actual irrigated area was found to be 18.92 km2 for which net irrigation demand was maximum in the month of June (3.61 MCM) followed by October month (0.12 MCM). Total net irrigation demand for actual irrigated area was 5.47 MCM. The computation of crop water requirement, NIR, and total net irrigation demand using CROPWAT has proved to be an effective tool for proper management of water resources in water stress condition.